Human Resource Development in the Digital Era: A Transformation and Competence Adaptation - Shidqi Mukhtar; Moh Shodoqin; Intan Ratnawati (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Digital transformation has become a key catalyst in reshaping human resource management practices, requiring organizations to continuously adapt employee competencies in response to rapid technological change. This study aims to examine the relationships between digital transformation, competency adaptation, and human resource development in contemporary organizational settings. The research adopts a qualitative design using a systematic literature review approach, synthesizing evidence from 50 reputable peer-reviewed journal articles published between 2020 and 2025. The findings indicate that organizational agility, leadership, and technological readiness serve as major antecedents enabling effective digital adaptation in human resource development. The results further show that digital transformation contributes to improved employee competencies, stronger innovation capability, and more sustainable workforce performance. However, the review also identifies several challenges, including technostress, digital fatigue, and job insecurity, particularly when digital initiatives are implemented without sufficient human-centered strategies. Overall, the findings highlight that successful human resource development in the digital era depends on a balanced integration of technological advancement, human capabilities, and ethical digital governance. This study offers a theoretical contribution by proposing an integrated framework linking digital transformation, competency adaptation, and human resource development, while also providing practical insights for organizations in designing adaptive, inclusive, and sustainable digital transformation strategies.